Responses to Critics: What Makes Mysticism Critical? (Or, What Makes Critique Mystical?). Issue 1 (14th March 2021) - Palmquist, Stephen R.
Abstract: After summarizing the content of my book, Kant and Mysticism (Palmquist 2019 ), I warn against four preliminary misconceptions. The book never argues that Kant viewed himself as a mystic, fully acknowledges Kant's negative view of mysticism, offers no comprehensive overview of mystical traditions, and aims to initiate a dialogue, not to have the final word. I then respond to the foregoing essays by the five critics.